Sustainability in Iranian traditional architecture in the case of Isfahan-central Iran - Mokhtarshahi Sani, Rafooneh (2008)
Iranian architecture like the architecture of almost all other developing countries is in the middle of big transformation and change. Through last centuries, Iranian traditional and vernacular architecture demonstrated distinctive characteristics of sustainability. Today in Iranian contemporary architecture, however, such characteristics either completely demolished and forgot or misused frequently. During the recent years, Iran also has faced energy crisis. Then, sustainable buildings are demanded more than ever specially in Iranian large cities. Related statistics show most of spent energy is using by urbanized areas and residential buildings. Consequently, in order to find the proper way of adaptation with immediate environment, investigating traditional architecture and it’s harmonize relationship with nature appear to be a useful way. On the other hand, Iran is a large country with diverse climatically conditions and as a result different vernacular and traditional architectures. In this variety, central part of Iran and its old capital city: Isfahan has had an essential role in Iranian culture and architecture. This city locates in the arid and semi arid part of Iran, however, the most important river of central Iran is divided the city in two parts. Therefore, the traditional architecture of this city contained the characteristics of both arid regions and riverside cities. The aim of present paper is to give an overview of vernacular/ traditional architecture in central part of Iran in the perspective of sustainability. Also investigating the unique architectural characteristics of Isfahan city is the other focus of study. In this inquiry, revision of this traditional architecture has been divided in two categories: urban layout in general and traditional housing in specific focus.